Establishing the Biblical Seminary of the Philippines institutional archives - Cruz, Luis Ezra D. (Animo Repository, 2018)
The purpose of the project is to establish a formal, working, and sustainable Biblical Seminary of the Philippines (BSOP) Institutional Archives. By ensuring that materials with lasting value to the organization are properly maintained through the archives, the BSOP’s institutional identity and memory shall be preserved and be made available to its community. Pertinent policies and documentation concerning the administration of the institutional archives as well as its functions, objectives, and scope were crafted and aligned with the relevant archival storage and preservation requirements of the organization. Likewise, specific policies concerning various archival functions such as appraisal and acquisition, accessioning, storage and arrangement, and reference and access were crafted and established to provide guidance to archives personnel and users. Materials that are collected and already in possession of the designated archivist were appraised for their archival value and those deemed to have lasting value to the organization were accessioned for proper recording. Other materials that are stored in various offices at the time of the project will be appraised at a later schedule. Thereafter, proper arrangement and storage of materials were done with the application of relevant archival principles. Lastly, further project phases for description as well as digitization of the archival materials and setting up of archives management database shall be done in the future.